2008
DOI: 10.2112/06-0752.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variation in Fish Assemblage in a Coastal Lagoon without Direct Contact with the Sea (Southeastern Brazil)

Abstract: The Cabiunas Lagoon is a narrow water body that is perpendicular to the sea and isolated Before 1991, the sandbank was sometimes opened for a few days by local residents, but enters by limited groundwater seepage or by overtopping the sea barrier in storms. In 1998 National Park was established, including the Cabiunas Lagoon. Studies on the structure a the fish assemblage were performed between 1991 and 1994; we carried out one year (200 toring of the lagoon to identify spatiotemporal variations in the lagoon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Fish density was manipulated by introducing 40 adult individuals of Hyphessobrycon bifasciatus (Ellis, 1911) (Characidae) into the enclosures achieving a final density of 13 ind. m -2 , which is similar to that found in the littoral region of the Cabiú-nas lagoon (Sánchez-Botero et al 2008). Fish were caught near the study location with a net and were conditioned for 1 d in a fish tank-net inside the lagoon to allow for recovery from the stress associated with capture.…”
Section: Methodssupporting
confidence: 63%
“…Fish density was manipulated by introducing 40 adult individuals of Hyphessobrycon bifasciatus (Ellis, 1911) (Characidae) into the enclosures achieving a final density of 13 ind. m -2 , which is similar to that found in the littoral region of the Cabiú-nas lagoon (Sánchez-Botero et al 2008). Fish were caught near the study location with a net and were conditioned for 1 d in a fish tank-net inside the lagoon to allow for recovery from the stress associated with capture.…”
Section: Methodssupporting
confidence: 63%
“…Thus, L. grossidens derived from freshwater lineages, where Jurengraulis juruensis was the basal lineages, the topology is fully resolved as follows: (Jurengraulis, (Amazonsprattus, (Anchoviella, (Pterengraulis, (Lycengraulis batesii, (L. poeyi, L. grossidens)))))) (Bloom & Lovejoy 2012). (Evermann & Kendall 1906, Hildebrand 1943, Menezes 1950, Fuster de Plaza & Boschi 1961, Vieira et al 1996, Benedito-Cecilio et al 1997, Saint-Paul et al 2000, Saad et al 2002, Joyeux et al 2004, Cervigón 2005, Ramos 2005, Bortoluzzi et al 2006, Burns et al 2006, Queiroz et al 2006, Loebmann et al 2008, Sánchez-Botero et al 2008, Costa & SouzaConceição 2009 (Figure 3 (Schultz 1949, Fuster de Plaza & Boschi 1961, Valdez & Aguilera 1987, Whitehead et al 1988, Albuquerque 1994, Santos et al 1998, Kullender & Ferraris 2003, Cervigón 2005, Guedes et al 2005, Silva 2006, Lira & Teixeira 2008, Santos et al 2008, Mai et al 2012 (Figure 3). …”
Section: Phylogenetic Relationshipsmentioning
confidence: 99%
“…In lower latitudes L. grossidens has usually been described as marine migrant or marine straggler (Vasconcelos-Filho & Oliveira 1999, Krumme et al 2004, Sánchez-Botero et al 2008, Reis-Filho et al 2010, Vilar et al 2011, although spawning activities were never reported for lower or higher latitudes in the marine environment. In contrast, the species shows the proven ability to reproduce in both fresh water (Fuster de Plaza & Boschi 1961, Oliveira 1997, Lepkoski et al 2005) and estuarine environments (Ramos 2005, Oliveira 2008).…”
Section: Final Conclusion and Future Research Directionsmentioning
confidence: 99%
“…According to one of them, C. parallellus, Hoplias malabaricus (Bloch, 1794) and Caranx latus Agassiz, 1831, are examples of predatory fish. According to the scientific literature, these three species feed on fish and invertebrates (Silvano 2001, Sá nchez-Botero et al 2008). The first two are piscivorous, both in number of food items and consumed biomass (Loureiro & Hahn, 1996, Toniniet al 2007), whereas C. latus eats both fish and invertebrates, but the consumed biomass of fish is higher than the invertebrates' (Silvano 2001).…”
Section: Ecological Aspects Of Ichthyofaunamentioning
confidence: 99%
“…at Mombaça, there is no more fish breeding''. The use of macrophytes by different fish species in coastal lagoons is highlighted by Sá nchez-Botero et al (2008). According to them, some species are highly dependent on such environments, for both feeding in juvenile or adult stages and for using macrophytes for parental fish eggs and larval care.…”
Section: Aquatic Macrophytesmentioning
confidence: 99%